1994
DOI: 10.1159/000117073
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis with Very Late Onset: Report of Six Cases and Review of the Literature

Abstract: Multiple sclerosis (MS) usually starts in young adulthood. However, the disease may appear late or very late in life. We report 6 cases with onset after the age of 59 years and review the literature. As in early onset disease, the diagnosis is mainly clinical. Laboratory findings and paraclinical evidence may support the diagnosis if clinical data are not sufficient. In elderly patients clinical history and laboratory data should be thoroughly appraised to exclude conditions more common in old age such as vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…[2][3][4][5] In some studies a cut-off age of 60 years has also been proposed for very late onset MS (VLOMS). 6,7 It remains uncertain whether patients with late onset MS (LOMS) constitute a distinct subset of MS with regard to clinical presentation and course. Some studies in Caucasian populations in the northern hemisphere reported that patients with LOMS were more likely to have motor and cerebellar presentations, a more progressive course and a worse prognosis than patients with earlier onset disease.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] In some studies a cut-off age of 60 years has also been proposed for very late onset MS (VLOMS). 6,7 It remains uncertain whether patients with late onset MS (LOMS) constitute a distinct subset of MS with regard to clinical presentation and course. Some studies in Caucasian populations in the northern hemisphere reported that patients with LOMS were more likely to have motor and cerebellar presentations, a more progressive course and a worse prognosis than patients with earlier onset disease.…”
Section: Introductionmentioning
confidence: 99%
“…The age of onset is older for primary progressive MS than for relapsing-remitting MS. 10 The clinical features of late-onset MS (≥60 years of age) compared with ordinary MS are as follows: a tendency for a decreasing female/male ratio, reduced incidence in family members, high frequency of motor function disturbances as the initial symptoms, shorter intervals between relapses, and gradual progression of the symptoms with less incidence of the relapsing-remitting variety, leading to severe disability. [3][4][5][6][7][8] The present case corresponds with the above clinical features except that remission of symptoms was achieved after steroid treatment, without her falling into disability.…”
Section: Discussionmentioning
confidence: 53%
“…The incidences in patients aged >50 years and >60 years are 1.3-9.4% and 0.6-0.75%, respectively. [1][2][3] Patients with late-onset MS experience a primary progressive course, often associated with a faster progression to disability, unlike young adults or juvenile patients [3][4][5][6][7][8] ; thus, it is sometimes diffi cult to diagnose MS during the lifetime of older patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, lateonset MS, defined as the first presentation of clinical symptoms after 50, has been reported to be in the range of 1.1-10.0% (Noseworthy et al 1983;Marra 1984;Safran 1989;White et al 1990;Azzimondi et al 1994;Polliack et al 2001;Delalande et al 2002). Importantly, a number of studies (Noseworthy et al 1983;Hooge and Redekop 1992;Azzimondi et al 1994;Trefouret et al 1996;Polliack et al 2001;Delalande et al 2002), albeit not all (White et al 1990), report a poorer prognosis and a more rapid progression to disability in late-onset MS patients compared to younger patients. This suggests that late-onset MS may represent a phenotypically and genotypically distinct subset of patients.…”
Section: Resultsmentioning
confidence: 99%